2010 bird´s eye view: scientific publishing, OA, indicators and infometrics - Aguillo, Isidro F. (Anuario ThinkEPI, 2011)
Review of the scientific publication situation in Europe and especially in Spain. Among other issues, infometrics, indicators, university rankings, databases, WoS and Scopus, and open access repositories are discussed.